Mott−Hubbard Lacalization in a Model of the Electronic Subsystem of Doped Fullerides - Dovhopyaty, Yu.; Didukh, L.; Kramar , O.; Skorenkyy, Yu.; Drohobitskyy, Yu. (Ukrainian Journal of Physics, 2012)
A microscopical model of doped fulleride electronic subsystem taking the triple orbital degeneracy of energy states into account is considered within the configurational-operator approach. Using the Green function method, the energy spectrum at the integer band filling n = 1 corresponding to AC60 compounds is calculated. A possible correlation-driven metal-insulator transition within the model is discussed.